The Impact of Buyback Announcement on Stock Anomalies in the Indonesia Stock Exchange - Arifin, Muhammad Hanief; Paramita, R.A. Sista (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This research aims to analyse the effect of buyback announcements on stock anomalies, as reflected in abnormal returns, cumulative abnormal returns, and trading volume activity. Design/methodology/approach: The sample data comprises 72 companies listed on the Indonesia Stock Exchange that made buyback announcements from 2020 to 2022. An event study methodology was employed to examine the buyback announcement events. Additionally, the Wilcoxon-Signed Rank Test was utilized as a statistical tool to test for differences before and after the buyback announcements. Research Findings: The results indicate no significant difference in abnormal return around the stock buyback announcement dates, no significant difference in cumulative abnormal return around the stock buyback announcement dates, and a significant difference in trading volume activity around the stock buyback announcement dates. Theoretical Contribution/Originality: This study contributes empirically and theoretically by emphasizing the impact of buyback announcements on stock anomalies for corporate managers and investors in decision-making strategies under conditions of economic uncertainty due to COVID-19. Keywords: Abnormal return, Buyback Announcement, Cumulative Abnormal return, Trading volume activity